After Guidelines, What? - Dennis M Bowie (Canadian Respiratory Journal)
In a recent survey, Canadian Thoracic Society (CTS) members indicated that they feel our association should be involved in the production of guidelines (1). There is evidence in the literature that suggests guidelines can have some effect in changing behaviour, although this is variable and modest at best. Certainly, the production of guidelines is not without costs, particularly in time spent by experts in reviewing the literature and producing them. For good reasons, delays frequently occur in their production, often leading to recommendations that may be outdated. People sometimes forget that one of the most important reasons for producing guidelines is to identify questions that require future research.